Food web of insects associated with the cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae), and its introduced parasitoid, Epidinocarsis lopezi (De Santis) (Hymenoptera: Encyrtidae), in Africa - Neuenschwander, Peter; Hennessey, R.D.; Herren, H.R. (Cambridge University Press, 1987)
About 130 species of parasitoids and predators are reported, most of them for the first time, to be associated directly or indirectly with the cassava pest Phenacoccus manihoti Matile-Ferrero and its parasitoid, Epidinocarsis lopezi (De Santis), newly introduced into Africa as a biological control agent. About 20 species are common. The species are grouped in 11 guilds, which include the indigenous hyperparasitoids, which originally attacked parasitoids of other mealybugs, the predators with which E. lopezi competes for the same food source and their antagonists.